081. Radiofrequency Ablation for Retrosternal Thyroid Tumour: A Rare Case Report - Soeseno, Stephen William; Irawan, Hendry (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p081, 2024)
Background : Retrosternal thyroid tumours, though uncommon, present complex diagnostic and therapeutic challenges due to their location behind the sternum. These tumours can cause significant symptoms, such as difficulty breathing and chest pressure, which can impact patient quality of life. Radiofrequency ablation (RFA) has emerged as a minimally invasive treatment option, offering potential benefits over conventional surgical methods for retrosternal thyroid tumor. Case: A 54-year-old male with a history of right thyroid isthmolobectomy presented with a rapidly growing left-sided neck mass, causing increasing chest pressure and shortness of breath. Imaging studies, including ultrasound and CT scans, revealed a large tumour extending retrosternally and compressing the trachea. The patient opted for RFA over surgery. A core biopsy confirmed a benign struma adenomatosa. RFA was performed using the moving shoot technique, resulting in effective tumor ablation. Follow-up imaging showed a significant reduction in tumor size and symptom relief. Conclusion: This case demonstrates that RFA is a safe and effective alternative to conventional surgery for retrosternal thyroid tumours. It provides substantial symptom relief and tumour reduction with fewer complications. RFA should be considered a valuable treatment option for patients who are not ideal candidates for surgery or who prefer less invasive approaches. Continued research and long-term studies are needed to confirm its broader efficacy.